DEVELOPMENT OF ANDROID-BASED 3D VIRTUAL GAME OF UNIVERSITAS MUHAMMADIYAH RIAU CAMPUS ADVENTURE - Dewi Odicia Clariesta Aziz; Al Rian, Rahmad; Benny Herlandy, Pratama (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2023)
The students of Universitas Muhammadiyah Riau (UMRI), both old and new, have problems in knowing the layout of the room at UMRI because the university combines several important faculties and rooms in one building, such as building A which has a Mathematics and Natural Sciences Faculty, Engineering Faculty, and Law Faculty. Therefore, this study aims to create a 3D virtual game of Universitas Muhammadiyah Riau campus adventure based on Android as a medium to help students in knowing the layout of the campus space and can train the students’ adventure skill in recognizing the campus environment virtually. This research utilizes Research and Development (R&D) with the ADDIE model. The ADDIE stages are Analysis, Design, Development, Implementation and Evaluation. Data was collected through a questionnaire (Likert scale) at the time of trial. The assessment results of media experts on the feasibility of 3D virtual game on campus adventure reached an average score of 3.88 in the excellent category. The assessment results from the evaluation of several Universitas Muhammadiyah Riau students' tests on the feasibility of 3D virtual game on campus adventure achieved an average score of 3.75 in the excellent category. Based on the results of research conducted, it was concluded that the 3D virtual game on Universitas Muhammadiyah Riau campus adventure was feasible to use.